High-resolution records of sulfur and insoluble particle concentrations from the B19 ice core in Greenland between 1530 and 1710 CE - Michael Sigl; Joseph R McConnell; Nathan J Chellman; Imogen Gabriel (PANGAEA, 2025)
We report high resolution (1 cm depth) sulfur concentrations from the B19 ice core in Greenland analyzed using inductively coupled plasma mass spectrometry (ICPMS) and mass concentrations of insoluble particles (5-10um size) using an inline Abakus® laser particle counter at the Desert Research Institute. Details about the analytical procedures are provided in the references. These records are used alongside ice-core crypto-tephra to characterize volcanic eruption sources in the 1660s CE.
In: Sigl, M et al. (2025): High time resolution records of sulfur and insoluble particle concentrations from five ice cores from Greenland and one from Antarctica between 1530 and 1710 CE and inferred volcanic contributions [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.974177